S. J. Keay, «Late Roman Amphorae in the Western Mediterranean. A typology and economic study: the Catalan evidence», BAR International Series, 196, 1984, XXVI+738pp., 230 figuras. Precio: 32 libras - CHAUSA Sáez, A. (Gerión. Revista de Historia Antigua, 1985)
Sin resumen